Numerical Investigation on Effect of Immersed Blade Depth on the Performance of Undershot Water Turbines - N. F., Yah; M. S., Idris; A. N., Oumer (EDP Sciences, 2016)
Energy, especially electricity, plays a vital role in global social and economic development. High annual rain rate in Malaysia seems a good potential for electricity generation especially through small hydro powers. Undershot water turbines are one of the hydropower turbines used for many years. However, the effect of blade depth immersed in the flowing water is not fully investigated. Therefore, the purpose of this paper is to study the effect of immersed blade depth for straight blade undershot water turbine in power generation by using Computational Fluid Dynamics (CFD) method. ANSYS CFX 15.0 was used to perform three dimensional analysis under steady state, incompressible, and non-isothermal conditions. The water wheel with number of blades of 6 and four different immersed depth was applied for each simulation. There are four different immersed depth was applied to each simulation, which are 20 mm, 40 mm, 60 mm and 80 mm. From the simulation result, it was found that the optimum immersed depth is 40 mm where the torque load and power generated were 0.264 N.m and 1.318 Watt respectively.